Total elbow arthroplasty surgery in neglected elbow stiffness post open reduction and internal fixation with plate and screw: a case report - Putra, I. Gede Mahardika; Karna, Made Bramantya (International Journal of Research in Medical Sciences, 2020)
Post-traumatic and post-operative stiffness of the elbow joint constitutes a significant problem since the elbow is prone to develop soft-tissue contractures and heterotopic bone formation especially if happened in dominant arm. Total elbow replacement is considered as an ultimate treatment in salvaging a stiff elbow which has failed conservative and operative therapeutic procedures to overcome the stiffness and return the elbow to an effective functional arc. A 35-year-old female came to orthopaedic outpatient clinic in Sanglah Hospital, complaining on stiffness in her right elbow since one year prior to admission. This complain was felt after she underwent internal fixation on July 19th 2016, for closed fracture right monteggia bado type-3 post internal fixation. After the surgery, she couldn’t move her elbow because of inappropriate physiotheraphy. Neglected elbow stiffness in this patient was treated surgically with total elbow arthroplasty after physiotherapy has failed to improve her range of motion over 1-year period postoperatively. This decision stated when nonsurgical treatment fails, the patient who has realistic expectations of eventual outcome and who can comply with the arduous postoperative rehabilitation program may be a surgical candidate. Total elbow arthroplasty conducted for these patients resulted in satisfying functional outcome with using quick disabilities of the arm, shoulder and hand (DASH) score improved from 81.8 to 43.2 postoperatively and no complication was reported.